2016
DOI: 10.2147/ndt.s93874
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year retrospective study of demographic, anamnestic, and clinical factors related to psychiatric hospitalizations of adolescent patients

Abstract: BackgroundPsychiatric emergencies of children and adolescents have greatly increased during the last years, but this phenomenon has not been studied in detail. The aim of this study was to analyze the correlation between acute psychiatric hospitalizations of adolescents and selected variables to highlight risk factors for psychiatric emergencies.MethodsThis retrospective research was conducted in the acute psychiatric public ward, Service of Psychiatric Diagnosis and Treatment (SPDT), and in the residential fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
7
15
0
3
Order By: Relevance
“…Consistent with existing studies, boys were more likely to exhibit aggression than were girls (McEachern and Snyder, 2012). In a 5-year retrospective study from Di Lorenzo et al (2016), aggressive behavior was the most frequent reason for psychiatric hospitalization among boys. This phenomenon is likely explained by "social role theory," whereby gender-related behavioral differences are culturally determined.…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with existing studies, boys were more likely to exhibit aggression than were girls (McEachern and Snyder, 2012). In a 5-year retrospective study from Di Lorenzo et al (2016), aggressive behavior was the most frequent reason for psychiatric hospitalization among boys. This phenomenon is likely explained by "social role theory," whereby gender-related behavioral differences are culturally determined.…”
Section: Discussionsupporting
confidence: 79%
“…While the overall prevalence of mental health conditions in youth has remained relatively stable [1], many recent studies have reported an increase in psychiatric emergencies in children and adolescents. Such increase has been noted in the United States [2][3][4][5], Canada [6][7][8], and Europe [9][10][11]. Over the same period, most countries have reduced the number of child and adolescent psychiatric inpatient beds [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto al intento suicida, no se hallaron datos estadísticamente significativos asociados al sexo, como los reportados en otros estudios (17,18) . Los trastornos psicóticos y del ánimo estuvieron más frecuentemente asociados a emergencias pediátricas infantiles a nivel local, en concordancia con estudios anteriores (10,11) .…”
Section: Discussionunclassified
“…Al respecto, los datos de este estudio indicaron que el sexo femenino tuvo hasta dos veces más riesgo de presentar algún trastorno del ánimo. Sin embargo, estos datos contrastaron con los reportados a nivel internacional, en donde los trastornos de conducta y trastornos de adaptación fueron los más frecuentes (18) . Un hallazgo particular del presente estudio fue que los trastornos de personalidad escalaron en el ranking de presentación como diagnóstico asociado a una emergencia psiquiátrica en la adolescencia, a pesar de ser diagnósticos establecidos para la población adulta, teniendo el sexo femenino hasta dos veces más riesgo de mostrarlo.…”
Section: Discussionunclassified